Merging Photocatalysis with Electrochemistry: The Dawn of a new Alliance in Organic Synthesis. Issue 49 (23rd October 2019) - Capaldo, Luca; Quadri, Lorenzo L.; Ravelli, Davide
Abstract: The merging of a homogeneous photocatalytic system with an electrochemical cell, having exchanged electrons as the only common point, has been recently demonstrated. This combination opens unexplored pathways in synthesis and allowed net‐oxidative photocatalytic processes to be realized in the absence of a chemical oxidant, including: 1) the C−H alkylation of heteroarenes and 2) the coupling of azoles with arenes in the presence of an electrogenerated photocatalyst. Abstract : E‐merging methods : The merging of a homogeneous photocatalytic system with an electrochemical cell has been recently applied to organic synthesis, allowing to realize net‐oxidative photocatalytic processes in the absence of a chemical oxidant.